Tumor lysis syndrome and infectious complications during treatment with venetoclax combined with azacitidine or decitabine in patients with acute myeloid leukemia. (June 2022) - Arora, Sankalp; Zainaldin, Carl; Bathini, Srilakshmi; Gupta, Udita; Worth, Sarah; Bachiashvili, Kimo; Bhatia, Ravi; Godby, Kelly; Jamy, Omer; Rangaraju, Sravanti; Diamond, Barry; Oliver, Josh D.; et al.
Abstract: Venetoclax (Ven) in combination with azacitidine or decitabine (hypomethylating agent; HMA) is the standard-of-care treatment for older (≥75 years) or intensive chemotherapy ineligible adults with newly diagnosed acute myeloid leukemia (AML). Tumor lysis syndrome (TLS) and infectious complications are two of the most concerning associated adverse events. We studied the real-world incidence and outcomes of these adverse events with HMA/Ven in AML patients. Our retrospective analysis included 106 patients (median age 70 years). Of these, 61 (58%) received HMA/Ven in frontline setting while 45 (42%) received in salvage setting. 19 (18%) met laboratory criteria for TLS, five (5%) developed clinical TLS (acute kidney injury). The median time to develop TLS was 2 days (range −2 to 4). During cycle 1, 29 patients (27%) were diagnosed with febrile neutropenia while 26 (25%) developed new infections. Median time to development of new infection was 10 days (1−25). Pneumonia was the most common infection (8%). Febrile neutropenia and/or new infection during cycle 1 was associated with poorer median overall survival compared to those without these complications (4.9 months vs 11.6 months; p = 0.03). In conclusion, incidence of TLS and infections was high in our cohort during initiation of HMA/Ven therapy. This data emphasizes the need for closer monitoring in these patients, especially during the first 7–10 days of treatment, which is often achieved in the inpatient setting. Highlights: 18% of AML patients in our cohort developed TLS with HMA/Ven treatment. Patients with TLS had higher baseline white blood cell count and marrow blast burden. Febrile neutropenia occurred in 27% of patients during cycle 1 of HMA/Ven. New infections developed in 25% of patients during cycle 1 of HMA/Ven. Infectious complications during cycle 1 of HMA/Ven led to poorer survival outcomes.